Soil column experiment and numerical simulation research of Pb migration process in the groundwater fluctuation zone based on HYDRUS - Qu, Jihong; Jiang, Jueyan; Zhang, Yifeng; Li, Yuepeng; Yan, Tiangang; Guo, Wei; Lu, Shibao (Frontiers in Environmental Science, 2022)
Groundwater level fluctuation alters hydrodynamic conditions and hydrogeochemical action, thus affecting the migration and transformation of pollutants. This study investigated the effect of groundwater level fluctuations on Pb migration processes. We selected two typical media, coarse sand and medium sand, for the soil column experiments and numerical simulations of the Pb migration process in the groundwater level fluctuation zone. The soil column experiments showed that when the contaminants were distributed at a 30-40 cm depth in the soil column, the Pb migrated into the water in the range of 20-45 cm in coarse sand, while the range of Pb migration in medium sand decreased to 30 cm-40 cm. We constructed a numerical model of Pb migration in the aeration zone–saturation zone coupled with water transport and solute transport by HYDRUS-1D. The model simulated the migration process of Pb in different amplitude and frequency of water level fluctuation and initial concentration of pollutants. The results show that the coarse sand column and medium sand column showed relatively noticeable changes in Pb concentration in water at 30-40 cm and 30-35 cm, respectively. The migration range and concentration of Pb in water are proportional to the medium particle size and the frequency of water level fluctuation, and inversely proportional to the magnitude of water level fluctuation. The Pb concentration in the water increased or decreased as the initial pollutant concentration of the medium increased or decreased. Its variation is basically the same as the variation of the initial contaminant concentration. The research results can provide a scientific basis for the remediation of heavy metal pollution in groundwater.